PERENCANAAN JEMBATAN “BERDIKARI” KALI GARANG - Deskhi Ardiono; Muhammad Kahfi Fattahillah; Sri Prabandiyani Retno Wardani; Suharyanto Suharyanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
This final project consists of redesign of Berdikari-Kali Garang Bridge by using Prestressed Box Girder Concrete. The construction method that is used in this project is segmental box girder. And for the prestressed system, the type of cantilever is based on the consideration of the length of this bridge which has 240 meters length, and is devided into 3 quarters, which are : 60 m + 120 m + 60 m. The design of this bridge begins with the explaination of the background for the choice of the bridge type, the purpose for this study is followed with the fundamental of design, which is analyzed is based on the BMS ’92. from the original data, the preliminary design is done by determining the main dimension of the bridge. In the initial phase, the design of load analyzed are used. Load analyze are self weight, dead load, additional weight, traffic load, and time analyze because of creep, and loss of prestressed. From the analyze, than did the allowable stress control. After, did the box reinforcement calculation, allowable deflection, shear calculation, strength and stability calculation which are crack moment control, limit moment, divided force, and torque. At the end of design stage is did the support design. Upon completion stage box, then do the structural design under the initial step to determine cross-sectional dimensions of the pillars and abutments plan which will be calculated ultimate load that will be used to analyze the strength of pillars and abutments. Recent stages of planning the foundation pillars and abutments. The end result of this planning and cross section shape. Where that will be calculated from the price of the building to be used.